2020
DOI: 10.1186/s12884-020-2801-x
|View full text |Cite
|
Sign up to set email alerts
|

Combining breastfeeding and work: findings from the Epifane population-based birth cohort

Abstract: Background: Return to work is often cited as a reason for early cessation of breastfeeding (BF). Our objectives were to study the time span during which women employed prior to pregnancy returned to work according to BF duration category, and to identify sociodemographic, behavioral and pregnancy characteristics of women who continued BF after returning to work. Methods: Information on BF mode and work status was prospectively collected in a French nationwide birth cohort up to 1 year after delivery. Time of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
(56 reference statements)
2
18
0
3
Order By: Relevance
“…Employed women with higher education levels may learn more about the benefits of breastfeeding and remain committed to it in various ways. Similar results were also found in an investigation conducted in France (Castetbon et al, 2020). One study exploring breastfeeding intention of female physicians suggested that breastfeeding duration of employed women might be influenced by health educators and found that their intentions and knowledge correlated with their breastfeeding initiation practices (Sattari et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Employed women with higher education levels may learn more about the benefits of breastfeeding and remain committed to it in various ways. Similar results were also found in an investigation conducted in France (Castetbon et al, 2020). One study exploring breastfeeding intention of female physicians suggested that breastfeeding duration of employed women might be influenced by health educators and found that their intentions and knowledge correlated with their breastfeeding initiation practices (Sattari et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…One study [34] examined staff employed in a diverse range of clinical and non-clinical occupations, including doctors, nurses, allied health, population health, administration, management, information technology, and domestic services, and found that clinical staff may have less flexibility in their daily workload due to patient demands, which could impact their ability to take regular lactation breaks; hence, flexible work options and lactation breaks were identified as the main factors that facilitate breastfeeding at work [34]. Many similar studies highlighted the need for a support system that encourages flexible working hours as a key determinant of breastfeeding initiation and continuation [34][35][36]. In our study, the use of a lactation room and breast-pumping breaks were significant predictors of continued breastfeeding for between one to six months and more than six months after returning to work among the two groups after adjusting for other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers working as farmers, artisans, and merchants were more likely to continue MOM provision after returning to work compared to mothers working as managers; mothers classified as intermediate employees and manual workers were less likely to continue MOM provision after returning to work compared to mothers working as managers [ 82 ]…”
Section: Tablementioning
confidence: 99%